Case Report: Primary solid pseudopapillary neoplasm of the ovary with “cholesteroma-like” denaturation - Zhao, Ziqing; Lin, Jiahui; Bai, Tingting; Liao, Hongfeng; Liu, Zhengjin (Frontiers in Oncology, 2025)
Solid pseudopapillary neoplasms (SPNs) primarily arise in the pancreas and are uncommon in the ovaries. Here, we present a case of ovarian-origin SPN. Alongside the typical solid and pseudopapillary structures, “cholesteroma-like” denaturation areas and tissue degeneration regions are also observed. Immunohistochemistry analysis demonstrates positive results for β-catenin (nucleus), CD99 (dot-like), CD56, and vimentin. Imaging studies rule out pancreatic or other origins. This study aims to enhance comprehension, diagnosis, and differential diagnosis of primary ovarian SPN among pathologists and clinicians, as well as to investigate the origin and management of primary solid pseudopapillary tumors in the ovary.